La Agenda 2030 y el desarrollo sostenible: reflexiones en torno a su naturaleza jurídica y aplicación en el derecho internacional por parte de los Estados y las empresas - Laura García-Martín (Revista Iberoamericana de Estudios de Desarrollo)
The 2030 Agenda was approved by the General Assembly in 2015. However, its resolutions are not legally binding, so it is unclear what kind of obligations it establishes and the possible international liability that would arise from non-compliance. Being an instrument of soft law or soft law, its application depends to a greater extent on the acceptance of the states, which is a political advantage that should not be underestimated. Also, soft law rules often drive the development of international law, helping to lay the foundation for codification and even facilitating the creation of customary international law. This article aims to analyze the legal nature of the Agenda from an international normative point of view and also examine how its content can be articulated in accordance with International Law for states and for companies as non-state actors whose role is key in achieving the Sustainable Development Goals (SDGs).